The cost of equity capital in a regulatory environment: an international comparison - Graham, Kyle Stephen (Department of Finance and Tax, 2015)
South Africa's electricity tariff determinations have been a matter of much public debate. This has been highlighted in popular media in South Africa, with above inflation increases in electricity tariffs allowed by the National Energy Regulator of South Africa (NERSA) in Multi-Year Price Determination (MYPD) 2 and MYPD 3. However these increases are below those applied for by Eskom. Estimating the cost of equity capital is a key element of the tariff determination process. This study therefore aims to evaluate the cost of equity methodologies used by regulators, and to assess whether NERSA's (South Africa) methodology is in line with international best practice. This study analysed the published cost of equity methodologies of 14 electricity regulators operating within developed and developing economies. A review of academic literature indicates that the Capital Asset Pricing Model (CAPM) understates the returns of low beta stocks, such as utilities. Furthermore, the Fama and French Three Factor model (FF3F) has been shown to have better explanatory power and results in higher estimates of the cost of equity. In spite of these empirical findings, this study found a preference for the CAPM among regulators, with no regulators using the FF3F model. The CAPM is selected due to its widespread use and the fact that it is simple to implement. This finding indicates that regulators are systemically under-compensating utilities for the risk undertaken. NERSA's (South Africa) cost of equity methodology was found to be in line with regulatory methodology, although its lack of consideration of alternatives and its relative lack of disclosure into the estimation does result in less transparency and potentially less reliable estimates of the cost of equity. Until a definitive answer has been reached, it is likely that the CAPM will continue to be used in a regulatory environment.